PELAKSANAAN SUPERVISI PEMBELAJARAN OLEH KEPALA SEKOLAH TERHADAP GURU, STUDI KASUS: SEKOLAH DASAR NEGERI DI JAWA TENGAH - Setyo Hartanto (Jurnal Kewidyaiswaraan, 2021)
Abstract Viewed from the point of view of the implementation of learning supervision by the principal, it contains important elements, including; competencies and main tasks of principal functions, increasing teacher competence, and improving the quality of learning for supervised teachers. The objectives of this study include: 1) getting an overview of the series of activities for the implementation of teacher learning supervision by school principals at public elementary schools in Central Java, 2) revealing the effect on improving the quality of learning for teachers who have been supervised through 6 indicators. This case study on the implementation of learning supervision by the principal involved 11 teachers and 10 principals. Data collection assisted by the form-office 365 application, virtual interviews using the Zoom application, WhatsApp, and direct telephone contacts. The author's data analysis is domain analysis (Spradley and Hubberman) and assisted by form-office 365. Results of research and discussion: Answers to the formulation of the problem 1 learning supervision by the principal has been intensively implemented in the school that is the research location, meaning that principals and teachers have carried out maximum performance and responsibility to maintain the quality of learning. The answer to the formulation of problem 2 is to assist teachers in developing learning media, improving the preparation of lesson plans, and developing pedagogical competencies as well as changing children's behavior to be better and more prepared to face learning. Based on the conclusions of the research above, an extract of the substantive theory was obtained, which is a crystallization of the research results: "Although it is not fully implemented properly in accordance with applicable regulations and is considered a routine activity by teachers, supervision carried out by school principals provides benefits to teachers, especially in solving problems that occur in the classroom.